Pre-service Teachers’ Beliefs about the Roles of Thesis Supervisors: A Case Study - Tapia Carlín, Rebeca Elena (GIST – Education and Learning Research Journal, 2014)
Trainee beliefs about the roles of thesis supervisors can exert an important influence on timely and successful completion of theses. This research article explores pre-service teacher beliefs about the roles of thesis supervisors through the analysis of their learning diaries. The aim of this study is to identify ways to improve supervisory practices in order to facilitate timely theses completion. Findings reveal that participants believe that the supervisor should motivate trainees to write their thesis, help them to select a promising topic, and provide advice on the research design, data collection and data analysis. In sum, candidates expect guidance in the writing of the entire thesis. The data also suggest that shaping students’ beliefs can improve the timely and successful completion of their theses and as a result improve graduation rate.